Exploring “Speak-O-Rama” as a public speaking module: A pilot study in an Islamic integrated primary school - Nurul Iman Ahmad Bukhari; Suhaida Omar; Abas, Athirah; Bazilah Raihan Mat Shawal; Wan Suzana Aafanii Adeeba Wan Ibrahim; Ariezal Afzan Hasssan; Noor Hisham Md Nawi (Australian International Academic Centre, Australia, 2017)
This paper describes the pilot study in implementing a public speaking module for a primary school level. The module development was structured according to ASSURE Model with the Communicative Language Teaching (CLT) as the basis used in designing the module activities. One group of Year 4 students from an Islamic integrated school was selected and the research method employed was the quasi-experimental research with pre and post-tests as well as interviews with the English teachers on the students’ performance and self-confidence. Students were also interviewed to identify their self confidence level before and after the implementation of the public speaking module. This research project is hoped to increase students’ oral proficiency along with increasing self-confidence in public speaking at a young age, and to propose the implementation of this module as reference in primary education.